2018
DOI: 10.2478/sjce-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Use of Adhesion Promoters in Asphalt Mixtures

Abstract: The purpose of asphalt binder as a significant binder in road constructions is to permanently bind aggregates of different compositions and grain sizes. The asphalt binder itself does not have suitable adhesiveness, so after a period of time, bare grains can appear. This results in a gradual separation of the grains from an asphalt layer and the presence of potholes in a pavement. Adhesion promoters or adhesive agents are important and proven promoters in practice. They are substances mainly based on the fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Amine-based chemicals, anti-stripping agents, are capable of enhancing water resistance especially, for limestone and granite/bitumen mix. In another study, [ 109 ] explored a polyamide promoter that is based on fatty acids. It was observed that the adhesive additives positively increase the adhesion of the asphalt binder, even after being supplied to the asphalt mixture in quite a small quantity (0.3 % of the asphalt's binder weight).…”
Section: Factors Affecting Bitumen Propertiesmentioning
confidence: 99%
“…Amine-based chemicals, anti-stripping agents, are capable of enhancing water resistance especially, for limestone and granite/bitumen mix. In another study, [ 109 ] explored a polyamide promoter that is based on fatty acids. It was observed that the adhesive additives positively increase the adhesion of the asphalt binder, even after being supplied to the asphalt mixture in quite a small quantity (0.3 % of the asphalt's binder weight).…”
Section: Factors Affecting Bitumen Propertiesmentioning
confidence: 99%
“…Figure 1. Factors affecting the level of transport noise [6] Factors affecting the level of transport noise Characteristics of the traffic flow [8][9][10][11][12][13] Characteristics of the environment [15,16,19] Traffic flow composition…”
Section: Refferences Reviewmentioning
confidence: 99%
“…In Brazil [11], USA [12], Serbia [13], Italy [14], Canada [15], Romania [16], India [17] and other countries [18] tens of thousands of kilometers of acoustic screens are installed. Slovakia, France and Germany use a noise-absorbing road surface to reduce the noise of car tires [19]. Embankment and green plantations are successfully used to reduce the sound level in the way of its dissemination [12].…”
Section: Atmospheric Pressurementioning
confidence: 99%
“…Therefore, it is necessary to ensure both passive and active adhesion of the bituminous binder to mineral materials, which makes it possible to make a class of materials -surfaceactive substances. By active adhesion we understand the ability of bitumen to adhere to stone material due to the formation and maintenance of a strong chemical bond even in the presence of water, in contrast to passive adhesion, where a reliable bond is ensured only with the surface of dry stone material [6,12,13].…”
Section: Introductionmentioning
confidence: 99%